Research of Shift Law of Tractor HMCVT based on Fuel Economy - Mingxi Bao; Xiangdong Ni; Qi Wang; Shiwei Kang; Xiaorui Peng; Guojie Xu; Xin Zhao (Jixie chuandong)
Through the analysis of tractor fuel economy index and the influence factors of tractor economical efficiency， a kind of fuel economy shift rule with tractor minimum fuel consumption and traction as the goal of most efficient is put forward. According to the optimal fuel economy of the tractor， combined with the structure and transmission characteristics of the hydraulic mechanical continuously variable transmission（HMCVT）， the requirements of realizing the fuel economy of the tractor are expounded. A kind of shift rule with optimum economical efficiency of HMCVT is explored， which taking ratio of engine fuel consumption to transmission efficiency of HMCVT is the smallest as the objective. By using the SimulationX， the simulation is carried on， it is concluded that the engine speed torque curves under various gear， through compared with outside the engine characteristic curve， can make all the gears are at the lowest fuel consumption economy area， and guarantee the stability of the speed of the tractor， conforms to the economical shift rule.